Book reviewed: Fenomenología del ser y del lenguaje. Autor: Germán Vargas Guillén. - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 2004)
Book reviewed: Fenomenología del ser y del lenguaje. Autor: Germán Vargas Guillén.